Penerapan model pembelajaran problem based learning untuk meningkatkan pemahaman konsep pada materi gaya dan gerak siswa kelas IV sekolah dasar - Rizkiandini, Regina; Hidayat, Wahyu; Hadianti, Yeni (COLLASE (Creative of Learning Students Elementary Education), 2025)
This research aims to determine the increase in understanding of the concept of force and motion in class IV elementary school students in learning using the Problem Based Learning (PBL) model. The method used in this research is a quantitative method. The research subjects were 30 class IV students at SDN Sirnagalih in Ngamprah District, West Bandung Regency. Data was obtained by giving pretest and posttest questions. Based on the research results, it can be concluded that the application of the Problem Based Learning (PBL) model has succeeded in improving the ability to understand concepts in fourth grade elementary school students. This is proven by the average N-Gain value obtained at 0.78 with high criteria. This means that the level of effectiveness of using the Problem Based Learning (PBL) model in increasing fourth grade elementary school students' understanding of concepts in force and motion material has a high level of effectiveness.